Mass spectrometry of aerosol particle analogues in molecular beam experiments - Fárník, Michal; Lengyel, Jozef (Mass spectrometry reviews, 2018)
Nanometer-size particles such as ultrafine aerosol particles, ice nanoparticles, water nanodroplets, etc, play an important, however, not yet fully understood role in the atmospheric chemistry and physics. These species are often composed of water with admixture of other atmospherically relevant molecules. To mimic and investigate such particles in laboratory experiments, mixed water clusters with atmospherically relevant molecules can be generated in molecular beams and studied by various mass spectrometric methods. The present review demonstrates that such experiments can provide unprecedented details of reaction mechanisms, and detailed insight into the photon-, electron-, and ion-induced processes relevant to the atmospheric chemistry. After a brief outline of the molecular beam preparation, cluster properties, and ionization methods, we focus on the mixed clusters with various atmospheric molecules, such as hydrated sulfuric acid and nitric acid clusters, Nx Oy and halogen-containing molecules with water. A special attention is paid to their reactivity and solvent effects of water molecules on the observed processes.
Keywords: acidic dissociation; atmospheric chemistry; molecular beams; clusters; ice nanoparticles; solvation